Overture of hope : two sisters' daring plan that saved opera's Jewish stars from the Third Reich - Vincent, Isabel, 1965- (Regnery History, 2022)
"Europe, 1937. Two British sisters, one a dowdy typist, the other a soon-to-be famous romance novelist. One shared passion for opera. With prospects for marriage and families of their own cut down by the scythe of World War I, the Cook sisters have thrown themselves into their love of music, with frequent pilgrimages to Germany and Austria to see their favorite opera stars perform. But now with war clouds gathering and harassment increasing, the stars of Continental opera, many of whom are Jewish, face dark futures under the boot heel of the Nazis. What can two middle-aged British spinsters do about such matters? They can form a secret cabal right under Hitler's nose and get to work saving lives. Along with Austrian conductor Clemens Krauss (a favorite of Hitler, but quietly working with the Cooks) the sisters conspire to bring together worldwide opera aficionados and insiders in an international operation to rescue Jews in the opera from the horrific fate that everyone intuits is coming. By the time war does arrive, the Cooks and their operatives have plucked over two dozen Jewish men and women from the looming maw of the Holocaust and spirited them to safety in England." -- Amazon.com.